2007
DOI: 10.1002/arch.20222
|View full text |Cite
|
Sign up to set email alerts
|

The DNA puff 4C expresses a salivary secretion protein in Trichosia pubescens (Diptera; Sciaridae)

Abstract: DNA puffs are genomic regions of polytene chromosomes that undergo developmentally controlled DNA amplification and transcription in salivary glands of sciarid flies. Here, we tested the hypothesis that DNA puff genes code for salivary proteins in Trichosia pubescens. To do that, we generated antibodies against saliva and immunoscreened a cDNA library made from salivary glands. We isolated clones corresponding to DNA puff regions, including clone D-50 that contained the entire coding sequence of the previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These studies led to the suggestion that DNA amplification was a mechanism that could rapidly provide high amounts of salivary gland proteins to build the cocoon in which the larvae pupariates. Indeed, most of the identified DNA puff proteins constitute secretion polypeptides present in salivary gland (de Almeida, ; Laicine et al ., ; Winter et al ., ) and studies employing polyclonal antibodies raised against different DNA puff proteins confirmed that DNA puff proteins are present in the saliva (Andrioli et al ., ; Fontes et al ., ; Monesi et al ., ).…”
Section: Initial Studies On the Biological Significance Of Dna Puffsmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies led to the suggestion that DNA amplification was a mechanism that could rapidly provide high amounts of salivary gland proteins to build the cocoon in which the larvae pupariates. Indeed, most of the identified DNA puff proteins constitute secretion polypeptides present in salivary gland (de Almeida, ; Laicine et al ., ; Winter et al ., ) and studies employing polyclonal antibodies raised against different DNA puff proteins confirmed that DNA puff proteins are present in the saliva (Andrioli et al ., ; Fontes et al ., ; Monesi et al ., ).…”
Section: Initial Studies On the Biological Significance Of Dna Puffsmentioning
confidence: 98%
“…DNA puff formation is temporally correlated with the abundant expression of DNA puff genes (Andrioli et al ., ; Fontes et al ., ; Frydman et al ., ; Paçó‐Larson et al ., ; Penalva et al ., ; Santelli et al ., ; Wu et al ., ). Several studies, both in vivo and in vitro have revealed that the hormone ecdysone regulates DNA puff gene expression (reviewed in Monesi et al ., ).…”
Section: Transcriptional Regulation Of Dna Puff Genesmentioning
confidence: 99%